The Mechanism by Which Dodecyl Dimethyl Benzyl Ammonium Chloride Increased the Toxicity of Chlorpyrifos to Spodoptera exigua - Cui, Li; Yuan, Huizhu; Yang, Daibin; Rui, Changhui; Mu, Wei (Frontiers in Pharmacology, 2017)
Beet armyworm, Spodoptera exigua (Hübner) is one of the most destructive pests that causes significant losses in crops. Unfortunately, S. exigua have developed resistance toward the majority of insecticides. Synergists may provide an important choice to deal with the resistance problems. Dodecyl dimethyl benzyl ammonium chloride (DDBAC) is a cationic surfactant, which displayed enhancement effect when combined with chlorpyrifos against S. exigua, giving enhancement factors of 1.50 and 1.57 at the concentrations of 90 and 810 mg L−1. In order to clarify the possible mechanisms, we investigate the effects of DDBAC on detoxification enzymes. However, DDBAC showed no inhibition on these enzymes activities. Meanwhile, scanning electron microscope images indicated DDBAC did not affect the cuticle super micro structure of S. exigua. The alterations in cuticular penetration rate have also been observed; indeed, it has been suggested that synergism is obtained by an acceleration of insecticide penetration through the cuticle. The chlorpyrifos penetration increased sharply when combined with 90 and 810 mg L−1 DDBAC, with only 12.6 and 8.5% of the initial chlorpyrifos recovered by external rinsing after 8 h. In contrast, when there was no DDBAC, more than 23.3% of the initial dose was recovered after 8 h.